EFIKASI VAKSIN DAN KEMANGKUSAN TETRASIKLIN UNTUK PENANGGULANGAN PENYAKIT MAS PADA PEMBESARAN LELE DUMBO (Clarias gariepinus) EFFICACY OF VACCINE AND THERAPEUTIC EFFECT OF TETRACYCLINE TOCONTROL MAS INFECTION : IN GROW - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT: The objective of study was to know the efficacy of vaccine and therapeutic effect of tetracycline medication to control MAS under field conditions. It was conducted in four separately locations namely : Cangkringan, Mlati, Experimental Pond of the-DepartMent of Fisheries, University of Gadjah Mada and Umbulharjo. All locations are fish-ifarrners pond except Experimental Pond. The results indicated that vaccination and tetracycline medication could increase survival rates 50,02% and 33,22% from control. Both the vaccination and medication could-also increase growth rates especially fish weight gain. Variation of survival and growth rates among locations were problably due to variation of field conditions, such as Water quality and degrees of Aeromonas hydrophila infections, and also the capability of fish -farmers.